LGG-44. Multi-omic analysis reveals integrated signalling networks in paediatric low-grade glioma. (3rd June 2022) - Woodward, Lewis; Jones, Tania A; Patel, Ankit; Dokal, Arran D; Stone, Thomas J; Rajeeve, Vinothini; Cutillas, Pedro R; Jones, David T W; Hargrave, Darren; Jacques, Thomas S; Sheer, Denise
Abstract: Paediatric low-grade gliomas (pLGGs) are the most common type of childhood CNS tumours. Our study included pilocytic astrocytomas (PAs; KIAA1549:BRAF), glioneuronal tumours (GNTs; BRAFV600E) and location-matched controls. We initially performed kinase substrate enrichment analysis (KSEA) to infer differential kinase activity, which allowed us to identify altered signalling networks in the two tumour types. Here we report the integration of these kinase signalling networks together with total proteomics, transcription factor enrichment analysis (TFEA) and transcriptomics (coding and non-coding). Total proteomic profiling confirmed an increase in proteins involved in cell cycle, inflammatory response and signal transduction in PAs, whilst there was an increase in proteins promoting cell growth, immune response and inflammation in GNTs. TFEA was performed using the DoRothEA database to identify master transcriptional regulators. We observed signiﬁcant activation of transcription factors (TFs) that are direct targets of MAPK signalling in both tumour types. Notable differences include the higher activation of NF-kB/STAT TFs in PAs and the increased activation of RFX1/2 in GNTs. Next, we constructed kinase-TF networks and identified multiple kinases targeting STAT3 in PAs and STAT1/3 in GNTs. Pathway analysis of RNA-Sequencing data showed enrichment of NF-kB in both tumours and repression of E2F target genes (PA) and reduced expression of MYC target genes (GNT). We developed a BRAF-OIS signature and found 23 genes commonly enriched in both tumour types, highlighting shared senescence-associated targets. MicroRNA profiling identified upregulation of microRNAs that target MAPK and NF-kB signalling networks, and many down-regulated microRNAs with tumour suppressive roles. Finally, we identified several lncRNAs known to be differentially expressed in glioma and, whilst their mechanism(s) of action are varied, they are thought to act with other well-established regulators to fine-tune cellular processes. Taken together, we present a comprehensive signalling network as a framework for studying pLGGs.